Heavy fermion behavior in the quasi-one-dimensional Kondo lattice CeCo2Ga8 - Le Wang (Nature Portfolio, 2017)
Heavy fermion materials: evidence for a quasi-one-dimensional Kondo lattice Evidence is provided for a heavy fermion material that is an unusual example of a quasi-one-dimensional Kondo lattice system. Heavy fermion materials are compounds with localised magnetic moments that interact strongly with the surrounding conduction electrons, causing a rich variety of exotic behaviour to arise. And when these moments form a periodic array, a Kondo lattice can be formed —where scattering off the moments becomes coherent. An international team of researchers led by Yi-feng Yang and Youguo Shi from the Institute of Physics, Chinese Academy of Sciences now present an unusual example of a Kondo lattice system that is quasi-one-dimensional in nature. Using a combination of experiments and first-principles calculations they show that the cerium atoms in single crystals of CeCo2Ga8 form chains, leading to quasi-one-dimensional Kondo lattice behaviour and unusual quantum critical scalings that are not expected in the conventional quantum critical theory.